Reliable fault classification of induction motors using texture feature extraction and a multiclass support vector machine - Uddin, Jia; Kang, Myeongsu; Dish, V. Nguyen; Kim, Jong-Myon (© 2014 Hindawi Publishing Corporation, 2016)
This article was published in the Mathematical Problems in Engineering [© 2014 Jia Uddin et al.] and the definite version is available at :http://dx.doi.org/10.1155/2014/814593 The Journal's website is at: https://www.hindawi.com/journals/mpe/2014/814593/